The Patterns of Religious Struggle Among Undergraduates Attending Evangelical Institutions. Issue 3 (27th May 2019) - Carter, Jennifer L.
Abstract: Of the 900 religiously affiliated colleges and universities in the United States, a sizable portion (approximately 118) are members of the Council for Christian Colleges & Universities (CCCU). As members of the CCCU, these institutions have a shared commitment to the academic and spiritual development of their students. However, relatively few studies have included data sets with multi-institutional types and longitudinal data. The purpose of this two-part study was to examine the patterns and predictors of religious struggle among traditional undergraduate students attending evangelical institutions compared to those at three other types of institutions. This article addresses the following question: How does the level of religious struggle change between the freshmen and junior years among college students attending evangelical institutions? A quantitative design using the 2004 and 2007 College Student Beliefs and Values Survey (CSBV)—which was last administered in 2007—with responses from 14, 527 students attending evangelical, Catholic, other religious, and nonsectarian institutions was employed. Results indicate that significant differences in the levels and patterns of religious struggle exist between evangelical institutions and other types of institutions. Longitudinal measures revealed that students from evangelical institutions experience higher levels of religious struggle compared to their peers at other types of institutions at the end of their junior year. This article is the first in a two-part series and focuses on the patterns of religious struggle among students attending evangelical institutions.